2022
DOI: 10.1021/acs.chemmater.2c02045
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Polymerization of Dihydrofuran Comonomer Facilitates Thermoset Deconstruction

Abstract: Frontal ring-opening metathesis polymerization (FROMP) is a rapid, low-energy manufacturing reaction that is useful for curing thermosetting materials. FROMP of dicyclopentadiene (DCPD) results in poly­(dicyclopentadiene) (p­(DCPD)), a tough thermoset with excellent mechanical performance and chemical stability. Like most thermosets, p­(DCPD) cannot be reprocessed and is therefore difficult to recycle. Previous work demonstrated that the incorporation of a small quantity of cleavable units in the strand segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…al. 89 p(DCPD) is a tough and chemically resistant thermoset that is often used for automotive application such as for body panels and bumpers for trucks, buses, and construction equipment. Davydovich et.…”
Section: Materials Extrusionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. 89 p(DCPD) is a tough and chemically resistant thermoset that is often used for automotive application such as for body panels and bumpers for trucks, buses, and construction equipment. Davydovich et.…”
Section: Materials Extrusionmentioning
confidence: 99%
“…Another recent development in sustainable high-performance materials for material extrusion is the use of degradable comonomers with thermosetting poly(dicyclopentadiene) ( p(DCPD)) by Davydovich et al 89 p(DCPD) is a tough and chemically resistant thermoset that is often used for automotive application such as for body panels and bumpers for trucks, buses, and construction equipment. Davydovich et al demonstrated that the incorporation of dihydrofuran (DHF) in DCPD resins allowed the printed pDCPD to degrade into oligomeric products with product recovery around 80%.…”
Section: Materials Extrusionmentioning
confidence: 99%
“…Several examples of copolymerization under phosphite dampened FROMP exist (Scheme 3). 145,147,148,151,168 Functionalized mono-norbornene and linked di-norbornene monomers underwent random copolymerization with DCPD. The heat associated with the homopolymerization of these monomers is given in Table 2; mono-norbornenes produce more heat per gram since the reactive olefin functionality represents a larger percentage of the molecular weight.…”
Section: Copolymerizationsmentioning
confidence: 99%
“…Davydovich et al 168 described frontal copolymerizations of DCPD and 2,3-dihydrofuran (DHF). Perhaps unsurprisingly, DHF dampens νf as it forms a less reactive Fischer carbene of the type [Ru=CH2OR] after ring-opening.…”
Section: Monomermentioning
confidence: 99%
See 1 more Smart Citation